2007
DOI: 10.1258/000456307782268084
|View full text |Cite
|
Sign up to set email alerts
|

Can serum free light chains replace urine electrophoresis in the detection of monoclonal gammopathies?

Abstract: AddressesBackground We investigated how sensitive serum free light chain (FLC) analysis was for the detection of Bence-Jones protein (BJP) and whether a serum k/l ratio could replace urine electrophoresis as part of the investigation algorithm for monoclonal gammopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 19 publications
0
39
0
1
Order By: Relevance
“…In the large screening studies by Hill et al (2006) and Katzmann et al (2006) two such patients were identified but none required medical intervention. Beetham et al (2007) also identified similar patients but did not correlate this with any clinical outcomes. These patients are likely to have MGUS with a small monoclonal FLC together with normal polyclonal FLC leaking into the urine presumably through damaged renal tubules.…”
Section: Serum Flc As a Marker Of Residual Diseasementioning
confidence: 92%
“…In the large screening studies by Hill et al (2006) and Katzmann et al (2006) two such patients were identified but none required medical intervention. Beetham et al (2007) also identified similar patients but did not correlate this with any clinical outcomes. These patients are likely to have MGUS with a small monoclonal FLC together with normal polyclonal FLC leaking into the urine presumably through damaged renal tubules.…”
Section: Serum Flc As a Marker Of Residual Diseasementioning
confidence: 92%
“…In the study by Hill et al 23 in the UK, there was an additional cost of $9 per patient to include the FLC assay. Since in many laboratories the initial blood sample is accompanied by urine Table 2 Rates of abnormal FLC ratio in different plasma cell disorders 21 there may be cost increases. Both patients and physicians are reluctant to do 24-h urine collections because of the inconvenience posed, but depending on the indication for the original monoclonal protein study of the blood, they could be missing at least 10-17% of cases with either AL amyloidosis or LCMM by doing serum IFE alone.…”
Section: Urine Flc Assaymentioning
confidence: 99%
“…Since we were intrigued by the potential use of the FLC analysis alone as a sensitive and rapid screening tool for Mproteinemia, as suggested in the paper from Abadie and Bankson (22), we studied the efficiency of the FLCs assay as a screening tool. It has been reported previously that reference values might be platform dependent (24,25). Thus, as a first step, we established local reference values using our Modular P analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reference ranges have been shown to be dependent on the platform used (24,25). To establish local reference values for the FLC assays, we selected samples from patients with a normal pattern assessed with SPE, and the absence of monoclonal bands in the IFE with pentavalent antiserum.…”
Section: Reference Valuesmentioning
confidence: 99%